Prevalence of neonatal sepsis and associated factors among neonates admitted in the neonatal intensive care unit at Lira Regional Referral Hospital, Northern Uganda - Brendah Katugume; JohnBaptist Muzungu; Nelson Okello; Eustes Kigongo; Deborah Andrinar Namutebi (PLoS ONE, 2025)
Background Sepsis is one of the leading causes of mortality and morbidity among neonates. An estimated 5.29–8.73 million Disability-adjusted life years (DALYs) are lost annually in SSA due to neonatal sepsis (NS). Uganda registered stagnated neonatal mortality of 27 deaths per 1000 live births in 2020 of which 12% was attributed to NS. Early risk factor identification and improved obstetric care are proven to reduce deaths due to NS, yet there is scanty literature on the LRRH. We, therefore, determined the prevalence of NS and identified its associated factors within the LRRH of northern Uganda. Methods A hospital-based, cross-sectional study with a retrospective chart review was conducted in the neonatal intensive care unit (NICU) at Lira Regional Referral Hospital (LRRH), in northern Uganda. 194 records of neonates admitted to the NICU from September 2022 to February 2023 were reviewed. The participant records were selected by systematic sampling technique and a structured data extraction tool was used to collect data. Using SPSS version 25 data entry and analysis were done. The univariable analysis gave a general description of the data. Logistic regression analysis was used to show associations and the statistical significance was declared at a P value of 0.05 after multivariable analysis. Results Among a total of 194 neonates whose charts were reviewed, 80 neonates had neonatal sepsis, giving a proportion of 0.412 and then prevalence of 41.2%. Age in days of the neonate (AOR = 4.212, 95% CI: [1.627-10.903]) for neonates of 1-3days of age, sex where males (AOR = 2.09, 95% CI: [1.123-3.887]), an APGAR score of 1-4 at birth (AOR = 0.309, 95% CI: [0.115-0.831]) and weight at birth <2500g (AOR = 2.543, 95% CI: [1.381-4.683]) were significantly related to it. Conclusions and recommendations The results found the prevalence of NS among neonates admitted to the NICU of LRRH high at 41.2%. Factors 1-3 days of age, male sex, a birth weight of <2500g, and an Apgar score of 1-4 at birth among all neonates were significant. Therefore, it was suggested that caregivers ensure safe newborn care, detect infections early, and use prophylactic antibiotics for high-risk babies after birth, to reduce NS. Further research will be conducted on the major causative agents and outcomes of NS in the NICU of LRRH.